Social services for persons with disabilities: theoretical approaches, comparative experiences and conditions and challenges in North Macedonia - Krstovski, Vlado (Ревија за социјална политика/Journal of Social Policy, 2019)
The new social policies aimed towards persons with disabilities are emphasising the need for transition from institutional to community-based care, through enabling social services that are following the human rights-based approach towards disability. The reform of the social services sector includes the paradigm shift regarding disability – from the medical and charity model towards social model and approach based on human rights. In the Republic of North Macedonia, the needed changes are development of the social services in the community, introduction of new quality standards, monitoring and evaluation of the community services, strengthening of the workforce capacity and training, awareness raising and advocacy, as well as user involvement in the whole process of service provision.